Historical institutionalism and the politics of sustainable energy transitions: A research agenda. (March 2017) - Lockwood, Matthew; Kuzemko, Caroline; Mitchell, Catherine; Hoggett, Richard
Improving the understanding of the politics of sustainable energy transitions has become a major focus for research. This paper builds on recent interest in institutionalist approaches to consider in some depth the agenda arising from a historical institutionalist perspective on such transitions. It is argued that historical institutionalism is a valuable complement to socio-technical systems approaches, offering tools for the explicit analysis of institutional dynamics that are present but implicit in the latter framework, opening up new questions and providing useful empirical material relevant for the study of the wider political contexts within which transitions are emerging. Deploying a number of core concepts including veto players, power, unintended consequences, and positive and negative feedback in a variety of ways, the paper explores research agendas in two broad areas: understanding diversity in transition outcomes in terms of the effects of different institutional arrangements, and the understanding of transitions in terms of institutional development and change. A range of issues are explored, including: the roles of electoral and political institutions, regulatory agencies, the creation of politically credible commitment to transition policies, power and incumbency, institutional systems and varieties of capitalism, sources of regime stability and instability, policy feedback effects, and types of gradual institutional change. The paper concludes with some observations on the potential and limitations of historical institutionalism, and briefly considers the question of whether there may be specific institutional configurations that would facilitate more rapid sustainable energy transitions.